PIPPA ENHANCES INTERNATIONAL 04 COLLABORATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 3 August 2015 – The Centre for Innovation and Productivity in Public Administration (PIPPA) of Universiti Sains Malaysia (USM) has earned international recognition for Malaysian public administration by becoming the first agency outside the United Kingdom to forge strategic cooperation with the Educational Competencies Consortium (ECC) in London.